Formulation and Evaluation of Buccoadhesive Drug Delivery System for Lovastatin - THENGE, RAJU RAMESH; Mahajan, S. S.; Mahajan, N. M.; Adhao, V.S.; Ajmire, P. V. (Journal of Drug Delivery and Therapeutics, 2019)
Lovastatin, a hyperlipedemic agent used in the treatment of hypercholesterolemia, has poor bioavailability ( less than 5%) due to the first pass metabolism and thus the dosing frequency is more, as a result of which several side effects occurred with the current dosage form. The present study aimed to formulate and evaluate buccoadhesive tablets of Lovastatin using mucoadhesive polymer such as Carbopol 934P, Hydroxypropylmethyl cellulose (K4M, K100M) and sodium CMC. The different formulations of buccoadhesive tablet of Lovastatin were prepared by direct compression method and characterized for physicochemical parameters such as thickness, content uniformity, weight variation, hardness, and friability test. The swelling index, % matrix erosion, surface pH, bioadhesive strength, bioadhesive time and in-vitro drug release are also carried out which has been important aspect for success of buccoadhesive tablets. The FTIR study was carried out for drug and polymer compatibility.  All the formulation showed satisfactory tablet properties. Formulation (F5) containing Carbopol 934P and HPMC K4M in the ratio of (1:1) showed good bioadhesive strength and maximum drug release of 95.80% in 8 hours. The surface pH of all tablets was found to be satisfactory, close to buccal pH, hence no irritation would observe with these tablets. FTIR studies showed no evidence of interaction between drug and polymers.Keywords: Buccoadhesive tablets, Lovastatin, FTIR, Carbopol 934P, in-vitro drug release